High-temperature CO denitration catalyst and preparation method thereof

By mixing rare earth tailings, carbon-based materials and acid-etched cordierite in a specific proportion to form a high-temperature CO denitrification catalyst, the existing SCR denitrification technology catalysts have solved the problems of high cost and high energy consumption, and the efficient, economical and environmentally friendly high-temperature denitrification effect has been achieved.

CN119819338APending Publication Date: 2025-04-15BEIJING YUZHI ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411653662.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing SCR denitrification technology catalysts have high cost, high energy consumption, long preparation cycle, high temperature inactivation, and prone to poisoning and failure.

Method used

Rare earth tailings, carbon-based materials and acid-etched cordierite are mixed in a specific proportion, and a high-temperature CO denitrification catalyst is formed through grinding and acid-etching treatment. The doped mosaic structure of rare earth elements and transition metal elements is used to generate active sites to improve catalytic activity.

Benefits of technology

It reduces the cost of catalyst, improves the efficiency of high-temperature denitrification, increases the adsorption capacity of NO and CO, avoids poisoning and inactivation, and realizes denitrification using CO in flue gas as a reducing agent, which is economical and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819338A_ABST
    Figure CN119819338A_ABST
Patent Text Reader

Abstract

The invention provides a high-temperature CO denitration catalyst and a preparation method thereof, and belongs to the technical field of catalyst preparation, and the high-temperature CO denitration catalyst comprises the following components in parts by weight: 1-10 parts of rare earth tailings, 1-10 parts of a carbon-based material and 30-50 parts of acid-etched cordierite. The rare earth tailings, the carbon-based material and the acid-etched cordierite are used as raw materials, the denitration efficiency of the catalyst can be improved while the cost of the catalyst is reduced, the preparation process is simple, energy consumption is low, the prepared catalyst is high in tolerance to water and SO2, poisoning and inactivation are avoided, pollution is avoided in the using process, SNCR can be replaced to a certain extent, and the method is suitable for industrial production. Therefore, ammonia water consumption and ammonia escape are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a high-temperature CO denitration catalyst and a preparation method thereof. Background Art

[0002] Nitrogen oxides (NOx) are a major atmospheric pollutant that causes a series of environmental problems such as photochemical smog, acid rain, and ozone layer depletion. As they cause great harm to the environment and human body, the laws and regulations of various countries to control nitrogen oxide emissions are becoming more and more stringent, and it is urgent to reduce or even eliminate their pollution.

[0003] At present, among many denitrification technologies, the one widely used at home and abroad is the ammonia selective reduction (NH3-SCR) technology, but it still has many shortcomings, so researchers have been committed to finding possible alternative technologies. CO is commonly found in industrial flue gases such as sintering and cement, and is an excellent reducing agent. Therefore, the use of CO selective catalytic reduction of NOx (CO-SCR) is considered to be one of the feasible technologies with great application potential. Its significant advantage is that CO and NO can be removed simultaneously through the catalyst, which is economical and environmentally friendly. At present, the CO denitrification catalyst under medium and low temperature conditions is more studied, mainly based on precious metals, but due to the high cost of precious metal catalysts, high temperature instability, easy poisoning, long preparation cycle and other disadvantages, it is difficult to be widely used. Therefore, the development of economical, efficient and safe high-temperature CO denitrification catalysts has become a research hotspot in recent years. Summary of the invention

[0004] The present invention aims to provide a high-temperature CO denitration catalyst and a preparation method thereof, so as to solve the problems of high catalyst cost, high energy consumption, long preparation cycle, high temperature deactivation and easy poisoning failure in SCR denitration technology.

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a high-temperature CO denitrification catalyst, which comprises, by weight: 1 to 10 parts of rare earth tailings, 1 to 10 parts of carbon-based materials, and 30 to 50 parts of acid-etched cordierite.

[0006] According to a preferred embodiment of the present invention, the carbon-based material is selected from at least one of biomass carbon, graphite powder and coke powder.

[0007] According to a preferred embodiment of the present invention, the rare earth tailings contain one or more elements of Fe, Mn, Ce, La, Nd, Nb, Pr, Zn, Co, P, K, Mg, Na, Ba, F, Si, Al, and S.

[0008] According to a preferred embodiment of the present invention, the mass percentage of each element in the rare earth tailings is: Fe element: 9.0-18.47%, Mn element: 0.13-3.49%, Ce element: 1.12-3.17%, La element: 12.00-20.67%, Nd element: 0.05-0.69%, Nb element: 0.03-0.47%, Pr element: 0.07-0.66%, Zn element: 2.56-4.88 %, Co element: 1.63~3.49%, P element: 0.88~1.17%, K element: 0.11~0.55%, Mg element: 1.11~4.30%, Na element: 0.33~1.45%, Ba element: 0.74~1.45%, F element: 6.45~12.79%, Si element: 5.06~12.10%, Al element: 0.91~2.25%, S element: 0.68~4.22%.

[0009] According to a preferred embodiment of the present invention, the rare earth tailings are selected from at least one of bastnaesite, monazite, xenotime, ion-adsorption rare earth ore and ferronithite.

[0010] According to a preferred embodiment of the present invention, the cordierite is selected from at least one of iron cordierite, cordierite and blood-spot cordierite.

[0011] In order to solve the above technical problems, the second aspect of the present invention provides a method for preparing a high-temperature CO denitrification catalyst, the method comprising:

[0012] crushing and grinding the rare earth tailings to obtain rare earth tailings fine powder;

[0013] grinding the carbon-based material to obtain a carbon-based fine powder;

[0014] Grinding cordierite into fine powder, mixing with oxalic acid solution, heating and stirring, filtering, washing and drying to obtain acid-etched cordierite;

[0015] grinding the acid-etched cordierite to obtain acid-etched cordierite fine powder;

[0016] A certain amount of rare earth tailings fine powder, carbon-based material fine powder, and acid-etched cordierite fine powder were weighed respectively and mixed to obtain a high-temperature CO denitrification catalyst.

[0017] In summary, the present invention utilizes a large amount of rare earth elements (Ce, La, etc.) and some transition metal elements (Fe, Mn, etc.) contained in rare earth tailings to inter-dope and inlay, and produces micro stress in the lattice, thereby generating a large amount of vacancy defect structures (i.e., active sites), and lattice oxygen is more likely to dissociate and migrate, becoming chemically adsorbed oxygen, forming oxygen vacancies. NO and CO are adsorbed on the active sites, promoting the fracture of NO bonds and the combination of CO and adsorbed oxygen, reducing the energy barrier of the reaction, thereby making the denitration reaction more likely to occur. At the same time, rare earth elements have the characteristics of 4f orbitals and lanthanide contraction that are not filled with electrons, and the most abundant light rare earth elements (lanthanum, cerium, praseodymium, neodymium, etc.) have abundant 4f empty orbitals, and when compounded with other components, obvious synergistic effects will be produced, and the basis for the synergistic catalytic effect between elements is also provided. In addition, the specific surface area of ​​rare earth tailings itself is small, and cordierite is mixed with rare earth tailings after acid washing and pore making, which can increase the specific surface area of ​​the mixed catalyst, thereby improving the adsorption capacity of NO and CO, and promoting denitration activity in a coordinated manner. At the same time, the carbon-based material can react with CO2 at high temperature to generate the reducing agent CO, which can increase the CO concentration in the atmosphere and improve the denitrification efficiency of the catalyst. Compared with the prior art, the present invention has at least the following beneficial effects:

[0018] 1. The present invention uses cheap and readily available general solid waste rare earth tailings as raw materials, which can reduce the cost of catalysts.

[0019] 2. The high-temperature CO denitrification catalyst prepared by the present invention can use the CO in the flue gas itself as a reducing agent to remove NO, without the need to add additional ammonia or urea, thus achieving waste treatment with waste, which is economical and environmentally friendly.

[0020] 3. The high-temperature CO denitrification catalyst of the present invention has a very high tolerance to water and SO2, thus avoiding poisoning and deactivation.

[0021] 4. The preparation process of the present invention is simple, does not require high-temperature calcination, and can greatly reduce energy consumption.

[0022] 5. The high-temperature CO denitration catalyst prepared by the present invention has a carbon-based material added that can react with CO2 at high temperature to generate a reducing agent CO, thereby increasing the CO concentration in the atmosphere and improving the denitration efficiency of the catalyst.

[0023] 6. The high-temperature CO denitrification catalyst prepared by the present invention has an extremely high denitrification effect at 900°C, and has an overlapping temperature zone with SNCR. It can replace SNCR to a certain extent, thereby reducing the amount of ammonia water used and ammonia escape. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic flow chart of a method for preparing a high-temperature CO denitration catalyst provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0025] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and Examples. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.

[0026] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0027] The invention provides a high-temperature CO denitration catalyst, which comprises, by weight: 1 to 10 parts of rare earth tailings, 1 to 10 parts of carbon-based materials, and 30 to 50 parts of acid-etched cordierite.

[0028] In a preferred embodiment, the carbon-based material is selected from at least one of biomass carbon, graphite powder, and coke powder.

[0029] In a preferred embodiment, the rare earth tailings contain one or more elements of Fe, Mn, Ce, La, Nd, Nb, Pr, Zn, Co, P, K, Mg, Na, Ba, F, Si, Al, and S.

[0030] Specifically, the mass percentage of each element in the rare earth tailings is: Fe element: 9.0-18.47%, Mn element: 0.13-3.49%, Ce element: 1.12-3.17%, La element: 12.00-20.67%, Nd element: 0.05-0.69%, Nb element: 0.03-0.47%, Pr element: 0.07-0.66%, Zn element: 2.56-4.88%, Co element: 0.05-0.69%, Nd element: 0.03-0.47%, Pr element: 0.05-0.69%, Zn element: 0.05-0.69%, Co element: 0.05-0.69%, Nd element: 0.03-0.47%, Pr element: 0.05-0.69%, Zn element: 0.05-0.69%, Cd ... Element: 1.63~3.49%, P element: 0.88~1.17%, K element: 0.11~0.55%, Mg element: 1.11~4.30%, Na element: 0.33~1.45%, Ba element: 0.74~1.45%, F element: 6.45~12.79%, Si element: 5.06~12.10%, Al element: 0.91~2.25%, S element: 0.68~4.22%.

[0031] In this embodiment, the rare earth tailings are selected from at least one of bastnaesite, monazite, xenotime, ion-adsorption rare earth ore, and ferroxene.

[0032] Wherein: the cordierite is selected from at least one of iron cordierite, cordierite and blood-spot cordierite.

[0033] Based on the above-mentioned high-temperature CO denitration catalyst, the present invention also provides a method for preparing a high-temperature CO denitration catalyst, such as Figure 1 , the method comprising:

[0034] S1, crushing and grinding the rare earth tailings to obtain rare earth tailings fine powder;

[0035] In this step, the rare earth tailings can be crushed, and the crushed blocks are ground with a ball mill to obtain 200 mesh fine powder for standby use.

[0036] Wherein: the rare earth tailings contain one or more elements of Fe, Mn, Ce, La, Nd, Nb, Pr, Zn, Co, P, K, Mg, Na, Ba, F, Si, Al, and S.

[0037] Specifically, the mass percentage of each element in the rare earth tailings is: Fe element: 9.0-18.47%, Mn element: 0.13-3.49%, Ce element: 1.12-3.17%, La element: 12.00-20.67%, Nd element: 0.05-0.69%, Nb element: 0.03-0.47%, Pr element: 0.07-0.66%, Zn element: 2.56-4.88%, Co element: 0.05-0.69%, Nd element: 0.03-0.47%, Pr element: 0.05-0.69%, Zn element: 0.05-0.69%, Co element: 0.05-0.69%, Nd element: 0.03-0.47%, Pr element: 0.05-0.69%, Zn element: 0.05-0.69%, Cd ... Element: 1.63~3.49%, P element: 0.88~1.17%, K element: 0.11~0.55%, Mg element: 1.11~4.30%, Na element: 0.33~1.45%, Ba element: 0.74~1.45%, F element: 6.45~12.79%, Si element: 5.06~12.10%, Al element: 0.91~2.25%, S element: 0.68~4.22%.

[0038] In this embodiment, the rare earth tailings can be selected from at least one of bastnaesite, monazite, xenotime, ion-adsorption rare earth ore, and ferroniusite.

[0039] Since a large number of rare earth elements (Ce, La, etc.) and some transition metal elements (Fe, Mn, etc.) contained in rare earth tailings are doped and embedded with each other, micro stress will be generated in the lattice, thereby generating a large number of vacancy defect structures (i.e., active sites), and the lattice oxygen will be more easily dissociated and migrated to become chemically adsorbed oxygen, forming oxygen vacancies. NO and CO are adsorbed on the active sites, promoting the breaking of NO bonds and the combination of CO and adsorbed oxygen, reducing the energy barrier of the reaction, thereby making the denitrification reaction easier to occur. The reaction mechanism is as follows:

[0040] NO (gas) → NO (ads)

[0041] CO (gas) → CO (ads)

[0042] NO (ads) → N (ads) + O (ads)

[0043] N (ads) + N (ads) → N2 (gas)

[0044] N (ads) + NO (ads) → N2O (ads)

[0045] N2O (ads) → N2 (ads) + O (ads)

[0046] CO (ads)+ O (ads) → CO2 (gas)

[0047] At the same time, rare earth elements have characteristics such as unfilled 4f orbitals and lanthanide contraction. In particular, the most abundant light rare earth elements (lanthanum, cerium, praseodymium, neodymium, etc.) have abundant 4f empty orbitals. When combined with other components, they will produce obvious synergistic effects, which also provides a basis for the synergistic catalytic effect between elements.

[0048] S2, grinding the carbon-based material to obtain carbon-based fine powder;

[0049] In this step, the carbon-based material can be ground using a ball mill to obtain 200-mesh fine powder for later use.

[0050] Wherein: the carbon-based material is selected from at least one of biomass carbon, graphite powder and coke powder. The carbon-based material can react with CO2 at high temperature to generate reducing agent CO, which can increase the CO concentration in the atmosphere and improve the denitrification efficiency of the catalyst.

[0051] S3, grinding the cordierite into fine powder, mixing with oxalic acid solution, heating and stirring, filtering, washing, and drying to obtain acid-etched cordierite;

[0052] In this step, the cordierite can be ground with a ball mill to obtain 200 mesh fine powder, and then the cordierite fine powder is mixed with 50% oxalic acid solution, heated and stirred for 2 hours, and then filtered, washed, and dried to obtain acid-etched cordierite.

[0053] Wherein: the cordierite is selected from at least one of iron cordierite, cordierite and blood-spot cordierite. After acid washing and pore formation, the cordierite will increase its specific surface area, and when mixed with rare earth tailings with a smaller specific surface area, the specific surface area of ​​the mixed catalyst can be increased, thereby improving the adsorption capacity of NO and CO and synergistically promoting the denitrification activity.

[0054] S4, grinding the acid-etched cordierite to obtain acid-etched cordierite fine powder;

[0055] In this step, the acid-etched cordierite can be ground by a ball mill to obtain 200-mesh fine powder for later use.

[0056] S5. Weigh a certain amount of rare earth tailings fine powder, carbon-based material fine powder, and acid-etched cordierite fine powder respectively, mix them, and obtain a high-temperature CO denitrification catalyst.

[0057] For example, 1 to 10 parts of rare earth tailings, 1 to 10 parts of carbon-based materials, and 30 to 50 parts of acid-etched cordierite can be weighed by weight, and they are fully stirred and mixed to obtain a high-temperature CO denitrification catalyst.

[0058] The high-temperature CO denitration catalyst and preparation method provided by the present invention are described in detail with specific examples below.

[0059] Example 1

[0060] Weigh 0 parts of rare earth tailings, 5 parts of carbon-based materials, and 40 parts of acid-etched cordierite, each with 200 mesh fine powder, and fully stir and mix them to obtain CO denitration catalyst sample 1;

[0061] The denitrification performance of the above sample 1 was evaluated using a fixed bed evaluation device. The flue gas distribution was simulated by a gas cylinder, and the gas conditions were 500ppm NO, 1000ppmCO, 40% CO2, 1% O2, 5% H2O, 150ppm SO2, and the remaining gas was nitrogen; the standard air velocity was 10000h-1; the temperature was 900℃;

[0062] A Fourier infrared flue gas analyzer was used to detect the changes in gas concentration before and after the reaction.

[0063] Example 2

[0064] Weigh 5 parts of rare earth tailings, 5 parts of carbon-based materials, and 40 parts of acid-etched cordierite, each with 200 mesh fine powder, and stir and mix them thoroughly to obtain CO denitration catalyst sample 2;

[0065] The denitrification performance of the above sample 2 was evaluated using a fixed bed evaluation device. The flue gas distribution was simulated by a gas cylinder, and the gas conditions were 500ppm NO, 1000ppmCO, 40% CO2, 1% O2, 5% H2O, 150ppm SO2, and the remaining gas was nitrogen; the standard air velocity was 10000h-1; the temperature was 900℃;

[0066] A Fourier infrared flue gas analyzer was used to detect the changes in gas concentration before and after the reaction.

[0067] Example 3

[0068] Weigh 10 parts of rare earth tailings, 5 parts of carbon-based materials, and 40 parts of acid-etched cordierite, each with 200 mesh fine powder, and stir and mix them thoroughly to obtain CO denitration catalyst sample 3;

[0069] The denitrification performance of the above sample 3 was evaluated using a fixed bed evaluation device. The flue gas distribution was simulated by a gas cylinder, and the gas conditions were 500ppm NO, 1000ppmCO, 40% CO2, 1% O2, 5% H2O, 150ppm SO2, and the remaining gas was nitrogen; the standard air velocity was 10000h-1; the temperature was 900℃;

[0070] A Fourier infrared flue gas analyzer was used to detect the changes in gas concentration before and after the reaction.

[0071] Example 4

[0072] Weigh 5 parts of rare earth tailings, 5 parts of carbon-based materials, and 40 parts of cordierite, each with 200 mesh fine powder, and stir and mix them thoroughly to obtain CO denitration catalyst sample 4;

[0073] The denitrification performance of the above sample 4 was evaluated using a fixed bed evaluation device. The flue gas distribution was simulated by a gas cylinder, and the gas conditions were 500ppm NO, 1000ppmCO, 40% CO2, 1% O2, 5% H2O, 150ppm SO2, and the remaining gas was nitrogen; the standard air velocity was 10000h-1; the temperature was 900℃;

[0074] A Fourier infrared flue gas analyzer was used to detect the changes in gas concentration before and after the reaction.

[0075] Example 5

[0076] Weigh 10 parts of rare earth tailings, 5 parts of carbon-based materials, and 40 parts of cordierite, each with a 200-mesh fine powder, and stir and mix them thoroughly to obtain CO denitration catalyst sample 5;

[0077] The denitrification performance of the above sample 5 was evaluated using a fixed bed evaluation device. The flue gas distribution was simulated by a gas cylinder, and the gas conditions were 500ppm NO, 1000ppmCO, 40% CO2, 1% O2, 5% H2O, 150ppm SO2, and the remaining gas was nitrogen; the standard air velocity was 10000h-1; the temperature was 900℃;

[0078] A Fourier infrared flue gas analyzer was used to detect the changes in gas concentration before and after the reaction.

[0079] The denitrification efficiency of samples 1 to 5 was tested and calculated according to the following formula:

[0080]

[0081] The performance test data of each denitrified catalyst sample of Examples 1 to 5 are shown in the table.

[0082] Sample No. Denitrification efficiency (%) <![CDATA[Specific surface area (m 2 / g)]]> Sample 1 20 125 Sample 2 82 113 Sample 3 97 104 Sample 4 69 12 Sample 5 85 11

[0083] Table 1: Performance test data of denitration catalyst samples

[0084] By analyzing the performance test data in Table 1, we can see that:

[0085] 1. Comparing denitration catalyst samples 1 to 3, the denitration efficiency increases with the increase of rare earth tailings content in the denitration catalyst;

[0086] 2. Comparing Sample 2 and Sample 4, Sample 3 and Sample 5, the specific surface area of ​​cordierite increases significantly after acid etching; the denitrification efficiency of the sample doped with acid-etched cordierite is higher than that of the sample doped with un-acid-etched cordierite. It can be seen that increasing the specific surface area of ​​the denitrification catalyst can improve its catalytic activity and efficiency.

[0087] It should be clear that the present invention is not limited to the specific structures and processes described above and shown in the figures. For the sake of simplicity, a detailed description of the known methods is omitted here. In the above embodiments, several specific steps are described and shown as examples. However, the method process of the present invention is not limited to the specific steps described and shown, and those skilled in the art can make various changes, modifications and additions, or change the order between the steps after understanding the spirit of the present invention.

[0088] It should also be noted that the exemplary embodiments mentioned in the present invention describe some methods or systems based on a series of steps or devices. However, the present invention is not limited to the order of the above steps, that is, the steps can be performed in the order mentioned in the embodiments, or in a different order from the embodiments, or several steps can be performed simultaneously.

[0089] The above is only a specific implementation of the present invention. Those skilled in the art can clearly understand that for the convenience and simplicity of description, the specific working process of the system, module and unit described above can refer to the corresponding process in the aforementioned method embodiment, and will not be repeated here. It should be understood that the protection scope of the present invention is not limited to this. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be covered within the protection scope of the present invention.

Claims

1. A high temperature CO denitration catalyst, characterized in that: The invention comprises, by weight: 1 to 10 parts of rare earth tailings, 1 to 10 parts of carbon-based materials, and 30 to 50 parts of acid-etched cordierite.

2. The high temperature CO denitration catalyst according to claim 1, characterized in that: The carbon-based material is selected from at least one of biomass carbon, graphite powder and coke powder.

3. The high temperature CO denitration catalyst according to claim 1, characterized in that: The rare earth tailings contain one or more elements of Fe, Mn, Ce, La, Nd, Nb, Pr, Zn, Co, P, K, Mg, Na, Ba, F, Si, Al, and S.

4. The high temperature CO denitration catalyst according to claim 1, characterized in that: The mass percentage of each element in the rare earth tailings is: Fe element: 9.0-18.47%, Mn element: 0.13-3.49%, Ce element: 1.12-3.17%, La element: 12.00-20.67%, Nd element: 0.05-0.69%, Nb element: 0.03-0.47%, Pr element: 0.07-0.66%, Zn element: 2.56-4.88%, Co element: 1.63~3.49%, P element: 0.88~1.17%, K element: 0.11~0.55%, Mg element: 1.11~4.30%, Na element: 0.33~1.45%, Ba element: 0.74~1.45%, F element: 6.45~12.79%, Si element: 5.06~12.10%, Al element: 0.91~2.25%, S element: 0.68~4.22%.

5. The high temperature CO denitration catalyst according to claim 1, characterized in that: The rare earth tailings are selected from at least one of bastnaesite, monazite, xenotime, ion-adsorption rare earth ore and ferronithite.

6. The high temperature CO denitration catalyst according to claim 1, characterized in that: The cordierite is selected from at least one of iron cordierite, cordierite and blood-spot cordierite.

7. A method for preparing a high-temperature CO denitrification catalyst, characterized in that: The method comprises: crushing and grinding the rare earth tailings to obtain rare earth tailings fine powder; grinding the carbon-based material to obtain a carbon-based fine powder; Grinding cordierite into fine powder, mixing with oxalic acid solution, heating and stirring, filtering, washing and drying to obtain acid-etched cordierite; grinding the acid-etched cordierite to obtain acid-etched cordierite fine powder; A certain amount of rare earth tailings fine powder, carbon-based material fine powder, and acid-etched cordierite fine powder were weighed respectively and mixed to obtain a high-temperature CO denitrification catalyst.

Citation Information

Patent Citations

  • Honeycomb integrated selective catalytic reduction (SCR) catalyst for nitric acid and nitrate tail gas denitration

    CN102614890A

  • Waste gas denitration composite catalyst and preparation method thereof

    CN107456981A

  • Method for denitrification of coal combustion high-temperature flue gas

    CN109173724A

  • Multifunctional Catalyst for Diesel Exhaust Gas Cleaning Applications and Method of its Preparation

    EP2145679A1